The Influence of Marketing Influence and Brand Ambassadors on Consumer Loyalty with Brand Personality as a Moderation of Mineral Water in Le Mineral Product Packaging - Diansyah; Yogatama, Rizky (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2024)
This study aims to investigate the relationship between marketing influence, brand ambassadors, and consumer loyalty, as well as the role of brand personality as a moderator in the relationship. The research method used is a survey with questionnaires distributed to a sample of consumers from various demographic backgrounds. This study focuses on the population of the community in the Greater Jakarta area with a sample of 125 respondents representing a predetermined population in answering questions related to the research variables. Data analysis was carried out using multiple regression techniques and moderator analysis. The results of the study show that marketing influence and brand ambassadors significantly affect consumer loyalty. In addition, brand personality has also been proven to moderate the relationship between marketing influence and brand ambassadors and consumer loyalty. These findings indicate the importance of paying attention not only to marketing strategies and the use of brand ambassadors, but also to brand characteristics in building consumer loyalty. This research contributes to the understanding of the factors that affect consumer loyalty in the digital era, by highlighting the important role of marketing influencers, brand ambassadors, and brand personalities. The practical implications of this research can help companies in designing more effective marketing strategies to maintain and increase their consumer loyalty.